Analisis Kinerja Kader Dalam Pelaksanaan Kegiatan Posyandu Di Wilayah Kerja Puskesmas Anak Air Tahun 2019 - Linda Raniwati; Ernawati Ernawati (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2025)
Introduction: Posyandu is a community based health effort that belongs to the community and is integrated into the life and culture of the community. Posyandu managers and implementers are cadres who have an important role in posyandu activities, therefore cadres must have good knowledge and skills in order to carry out their performance well in posyandu services. Objective: Analyzing the performance of cadres in implementing integrated health post activities Method: Qualitative research design, by means of in depth interviews with the village secretary, RW head, dasawisma head, regional coordinator midwife, while focus group discussions (FGD) with 10 posyandu cadres. Results: Based on the results of interviews conducted by cadres and the working group sector, it was analyzed that the integrated health post cadres had received training and received monthly incentives from the working group, but the facilities and infrastructure at the integrated health post in the working area of the Anak Air Health Center were inadequate, so that in carrying out integrated health post activities, they did not meet the standards (five tables) for integrated health post services.Conclusion: Informants in providing information are almost the same between cadres and working group elements, it is hoped that working groups will seek assistance with the facilities and infrastructure needed in integrated health post activities, so that cadres are able to carry out their performance properly and correctly according to integrated health post guidelines in an effort to improve the health of the community.